Control interno y su influencia en el cumplimiento de procesos de producción de la empresa wilpac s.a. del cantón Quevedo. Año 2022 - Pillasagua Cedeño, Cinthia Janina (2024)
The objective of this research focuses on the impact of internal control compliance following production processes in the company WILPAC S.A., exploring the relationship between these variables on production processes, and analyzing how internal control practices and mechanism impact the quality, efficiency and consistency of production in this organization; in addition, regulatory compliance is essential in many industries, and assessing how internal control affects this compliance can help avoid legal sanctions. Identifying deficiencies in internal control allows the company to implement continuous improvements and increase productivity over time. Through an exhaustive study, we identified areas for improvement in internal control that can strengthen WILPAC S.A.'s capacity. The universe of the research was the 26 officials from the management the administrative and financial department, the production department and the warehouse area of the company WILPAC S.A., who participated in the research deductive and inductive through internal control questionnaires using the COSO 1 MODEL was used to obtain the information. This research work was based on a detailed approach with the specific business context and provided a critical view of the importance of internal control in the management of production processes in an organization. The results allowed identifying the key to the management of internal control in the fulfillment of production processes in WILPAC S.A. in the city of Quevedo.